Smartphone Aid: Widget Application for Elderly People - Robert, Sri Santha Smrity (IRC, 2020)
This report presents an idea on developing a mobile application with widget engine to aid elderly people in Malaysia, especially to help in their daily life routine as well as during emergency situations. This idea was chosen due to some critical situation today where elderly people are struggling to cope up with the need of smartphones in daily lives. In relation with that, a mobile application with widget engine is planned to be developed specially for these elderly people to help them in using smartphone in their day-to day life without depending on the assistance of a secondary individual. To address this issue, my research paper focuses on coming up with the said mobile application with widget engine which highly encourage elderly users to use it in their smartphone for a better smartphone experience. The main issue that smartphone manufacturers and/or society need to understand from this idea is that even though smartphone features are growing tremendously in fulfilling the user requirements, they are not always quite the elderly-friendly features. The goal is to develop a mobile application with widget engine that assist the elderly users to use their smartphone according to their preferences so that they are not left behind by the quickly advancing technological world. Even though there are some similar mobile application available online, they are not specifically developed for elderly people, does not synch with all important applications found in the smartphone (such as contacts, reminder, etc) and also some of those widgets need to be purchased in order to use them, thus, I have plan to come up with an effective mobile application with widget engine where targeted users are highly encouraged and attracted to use it. Looking at one of the current technological issue, it has driven me to choose this particular topic to develop the said mobile application with widget engine as a prototype to show the smartphone manufacturers about this project concept. At the end of this project development, I hope that smartphone manufacturers and/or society are more aware on the problems faced by the elderly people while using smartphone.